Effect of ball milling on the mechanical properties and crystallization of graphene nanoplatelets reinforced short chain branched‐polyethylene. Issue 35 (15th April 2021) - Kourtidou, Dimitra; Grigora, Maria Eirini; Tsongas, Konstantinos; Terzopoulou, Zoe; Tzetzis, Dimitrios; Bikiaris, Dimitrios N.; Chrissafis, Konstantinos
Abstract: Short‐chain‐branched‐polyethylene (SCB‐PE) is extensively used in domestic hot and cold piping systems. SCB‐PE nanocomposites using graphene nanoplatelets (GNPs) as a filler, were prepared in this work. The effect of ball‐milling as a premixing technique prior to melt‐mixing, on the crystallization and the nanomechanical properties of the composites has been studied. Two sets of SCB‐PE/GNPs nanocomposites with various filler loadings were prepared; one with and one without the ball‐milling step. The dispersion of the filler was evaluated by optical microscopy while the crystallization process was studied using differential scanning calorimetry. The nonisothermal crystallization's experimental data were analyzed using various methods. The materials' nanomechanical behavior was investigated by conducting nanoindentation tests. A finite element analysis process was developed to extract the composites' stress–strain behavior. The composites prepared with ball‐milling presented improved dispersion of GNPs in the SCB‐PE matrix, which affected the crystallization, while nanoindentation tests showed significantly enhanced mechanical properties. Abstract :